"Because I have my phone with me all the time": The role of device access in developing Singapore adolescents' critical news literacy. Issue 5 (15th March 2023) - Loh, Chin Ee; Sun, Baoqi; Weninger, Csilla
Abstract: Given constant online access to information, critical news literacy, or the ability to access and critically evaluate the news, is essential for adolescents to learn about the world and obtain civic knowledge to participate as national and global citizens. Although there has been much research focusing on how youths critically read and produce media, less attention has been paid to the issue of access as an essential element of news literacy. Drawing on survey data ( N = 5732) and focus group discussions ( N = 67) with Singapore adolescents aged 13–17 years old, this study examines (1) whether adolescents access the news and if so, via what technologies, and (2) the factors that influence their news access. Findings show that adolescents prefer to read news online and that older adolescents (aged 15–17 years old) read more than younger adolescents (aged 13–14 years old). Factors shaping access to news include technological (portability, personalization, curation, and notifications), social (families, peers, and schools as sponsors), and personal factors (active seeking of news vs. incidental news exposure). Policymakers, scholars, and educators should consider the physical, social, and curatorial dimensions of news reading to implement policies and design practices to encourage news access and exposure. Educators can foster adolescents' motivation to read news by engaging them with news of interest to them, creating opportunities for them to receive the news through their smartphones and other devices, and developing their civic knowledge base.